Quantifying Airport Employee Commuting and Related Energy Use: A Comparison of Six US Airports - Daniel Zimny-Schmitt; Joshua Sperling (Findings, 2020)
There has been growing research interest in understanding the energy signatures of airport access and egress as air travel continues to grow. However, these findings generally focus on airport access from the perspective of air travelers rather than ground access modes by airport employees. Using a data set of employment records, this paper uses residential location data of airport employees to estimate the energy implications of employee commuting at six major US airports based on commuting mode choice information from the US Census. This analysis reveals a high degree of variance in commuting energy usage by employees between different airports.